PUBLIC PERCEPTION OF STATE OFFICIAL ETHICS: A CASE STUDY OF THE POST-DEMAND OF AUGUST 2025 - Sania Nusantari Setiawan (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
The ethics of state officials are a fundamental pillar in building and maintaining public trust, which serves as the foundation for the legitimacy and effectiveness of governance. In Indonesia, there is a gap between public expectations of officials' integrity and the reality of political practices, which are often tainted by abuse of power, corruption, collusion, nepotism (KKN), and the degradation of communication ethics. The massive demonstrations in August 2025 acted as a marker of the crisis, reflecting the public's deep disappointment with the behavior and policies of officials. The public perceives officials' ethics not merely as formal legal compliance but more as a manifestation of moral values, honesty, and civility in political life. This study employs a qualitative method with a case study approach to explore the public's subjective experiences in interpreting officials' ethics following the demonstrations. This study reveals a moral dissonance between public normative expectations and the actual behavior of officials. This experience shapes a negative collective memory while also triggering a new critical awareness to conduct more active social oversight. The research findings indicate that an ethical crisis not only damages individual reputations but also systemically undermines the legitimacy of government institutions. The study concludes that without comprehensive and ongoing ethical reform efforts, the erosion of public trust will continue, widening the gap between the state and its citizens. By addressing current issues, this research is expected to serve as material for critical reflection and provide practical recommendations for researchers and policymakers in efforts to strengthen the governance of integrity.